(untitled) (REMUNOM, 2026)
The oral health of patients admitted to Intensive Care Units (ICU) presents specific challenges, culminating in an increased risk of nosocomial infections. The oral cavity, compromised by factors such as deep sedation and mechanical ventilation, rapidly transforms into a reservoir of pathogens, favoring the aspiration of secretions and the subsequent Ventilator-Associated Pneumonia (VAP). This review article delves into: (1) the physiopathological particularities of the critical patient’s oral health and the mechanisms of oropharyngeal colonization; (2) the irreplaceable role of the dental surgeon in the ICU team, detailing their preventive interventions; (3) the mechanisms of antimicrobial resistance facilitated by oral biofilm; and (4) the latest evidence on the effectiveness of oral hygiene protocols combining mechanical removal and antiseptic agents in reducing VAP. It is concluded that the institutionalization of rigorous oral hygiene protocols including toothbrushing, supervised or performed by a hospital dentist, and the judicious use of antiseptics (mainly 0.12% chlorhexidine) are cost-effective measures that drastically reduce the incidence of VAP. It is crucial, however, that further studies focus on the impact of these interventions on outcomes such as mortality, length of stay, and the emergence of bacterial resistance.